1985
DOI: 10.1111/j.1365-2141.1985.tb07334.x
|View full text |Cite
|
Sign up to set email alerts
|

The storage pool deficiency in platelets from humans with the Chédiak‐Higashi syndrome: study of six patients

Abstract: Functional and biochemical studies of platelets from human Chédiak-Higashi syndrome (CHS) are scarce and/or incomplete. In the present report, the aggregation response to a variety of inducers of platelet aggregation, the content of the dense granule constituents ATP, ADP, serotonin and calcium, the secretion of ATP, ADP, and calcium induced by thrombin, the total content of magnesium, the incorporation of 14C-adenine in the cytoplasmic pool of adenine nucleotides, as well as the content of intracellular cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

1986
1986
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 28 publications
0
22
0
1
Order By: Relevance
“…Clinical diagnosis is firstly supported by the presence of peroxidase-positive giant inclusions in white blood cells, by detection of pigment clumping in the light microscopy analysis of hair and eventually by studies revealing abnormal platelet aggregation [14]. Electron microscopy can demonstrate reduced number and irregular morphology of platelet dense-bodies [29,30]. Of note, giant granules resembling those seen in CHS may be revealed in acute and chronic myeloid leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical diagnosis is firstly supported by the presence of peroxidase-positive giant inclusions in white blood cells, by detection of pigment clumping in the light microscopy analysis of hair and eventually by studies revealing abnormal platelet aggregation [14]. Electron microscopy can demonstrate reduced number and irregular morphology of platelet dense-bodies [29,30]. Of note, giant granules resembling those seen in CHS may be revealed in acute and chronic myeloid leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of secretion in platelet function is emphasized by the bleeding tendencies seen in patients with storage pool disease. [4][5][6][7] Multiple studies have shown that both increase in intracellular calcium and activation of protein kinase C (PKC) are required to mediate granule release. [8][9][10][11][12][13][14][15] Following platelet activation, tyrosine phosphorylation events of many proteins ensue.…”
Section: Introductionmentioning
confidence: 99%
“…2A). Besides, in human patients with CHS, impairment of epinephrine-induced aggregation was also observed [1,5,12]. Platelet aggregation by ADP is normal or sometimes slightly decreased with a tendency to disaggregate in CHS platelets.…”
Section: Structural or Functional Abnormalities In Chs Plateletsmentioning
confidence: 99%
“…A decrease in TXA 2 production could be a case in human CHS platelets because aggregation to exogenous arachidonic acid, which is converted to TXA 2 , was reported to decline in two human CHS cases [1,73]. Suzuki et al suggested that impairment of …”
Section: Structural or Functional Abnormalities In Chs Plateletsmentioning
confidence: 99%